2016
DOI: 10.1007/s10823-016-9300-6
|View full text |Cite
|
Sign up to set email alerts
|

Intention to Use Long-Term Care Facilities: Differences beween Korean Pre-elderly and Korean Baby-boomers

Abstract: With the rapidly increasing number of older adults, dealing with long-term care (LTC) needs becomes an emerging issue in South Korea. This study aims to examine factors affecting the intention to use longtermcare facilities with two groups of young-old adults: (1) Korean pre-elderly (KPE) and (2) Korean babyboomers (KBB). Guided by Andersen’s behavioral model of health service use and prior research, predisposing characters, enabling resources, need factors, availabilities of informal care and self-care activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 22 publications
(39 reference statements)
3
6
0
Order By: Relevance
“…Physical health was found to be negatively related to NLTC in this study. This is similar to the research carried out among Japanese elderly [6] and Korean elderly [14], which also found a negative association between physical health and NLTC. Meanwhile, previous researches conducted in the United States of America [8,57] and the United Kingdom [9] also found that having comorbid physical health problems (number of chronic diseases, pain/discomfort) was associated with a higher probability of NLTC.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Physical health was found to be negatively related to NLTC in this study. This is similar to the research carried out among Japanese elderly [6] and Korean elderly [14], which also found a negative association between physical health and NLTC. Meanwhile, previous researches conducted in the United States of America [8,57] and the United Kingdom [9] also found that having comorbid physical health problems (number of chronic diseases, pain/discomfort) was associated with a higher probability of NLTC.…”
Section: Discussionsupporting
confidence: 91%
“…The negative relationship found in this study between SES and NLTC is similar to the results of research conducted in Canada [53], Japan [54], and Vietnam [13], which found the SES and its indicators were shown to be determinants of NLTC. To be specific, the association between education and NLTC was similar to the result of Hong’s study carried out among Korean elderly people [14]. While the relationship between income and NLTC was similar to that of Hamada’s research conducted among Japanese older adults [15].…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Sawyer and Claxton (2019) reported that 42% of the population (45 year old and older) explains 69% of healthcare spending and 29% of the population (55 year old and older) accounted for 56% of healthcare spending among USA adults. The aging population's socio-demographic transition toward reduced fertility and increased mortality results in increased medical-care or healthcare costs and forces private and public sectors to grapple with healthy lifestyles (Health Insurance Review and Assessment Service, 2019; Gingiss, 2019), especially with baby boomers (Hong et al. , 2016; Jang, 2017).…”
Section: Methodsmentioning
confidence: 99%
“… 6 , 12 - 14 ) Individuals' personal preferences may differ regarding receiving care at home (formal or informal) or in an institution. 15 - 17 ) Several studies have reported that individuals who live alone, women, and younger people prefer institutional care. 13 , 18 ) In contrast, men generally prefer informal care.…”
Section: Introductionmentioning
confidence: 99%